Comparative Study of Learning Models and Teaching Materials on Student Cognitive Learning Outcomes - Nisa Pangsuma; Wahyu Surakusumah; Yayan Sanjaya (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Increasing student learning outcomes is one of the benchmarks in evaluating the implementation of the learning process. This research aims to test the effectiveness of learning models and approaches (PBL, PjBL, STEM) as well as teaching materials (E-modules and textbooks) in improving student learning outcomes. Where learning models and approaches and several types of teaching materials will be compared on student learning outcomes. So we will know the interaction of learning models and approaches and teaching materials used in influencing student learning outcomes. The research method used is comparative with experimental design. The samples used were 6 research classes selected using purposive sampling techniques. Research findings show that there is a significant influence between learning models and teaching materials on student learning outcomes, especially on the topic of biodiversity. Therefore, it is important to choose learning models and teaching materials that are relevant to the learning objectives.